Polskie nazwy służebne związane z funkcjonowaniem i ochroną średniowiecznych szlaków komunikacyjnych - Sosnowski, Jan; Witczak, Krzysztof Tomasz (Slavia Occidentalis, 2016)
The article focuses on two different categories of Old Polish service peasants, which were connected with operating and maintaining medieval routes (roads) in the Polish state under the early Piast dynasty. The first question, discussed by the authors, refers to the Polish place name Czastary (Wieluń district), which seems to represent a service village, inhabited earlier by “road-workers” (Lat. stratifices) originally called *castari (<Proto-Slavic *cěstarjь, pl. *cěstarji). The second problem concerns Old Polish “bridge-makers”. It is suggested, on the basis of the toponomastical data (see three Polish place names Bierwce, Bierniki and Biernik), that the peasants who were obliged to create bridges or foot-bridges, were called *bi(e)rwci (<Proto-Slavic *brъvьсi) or *bi(e)rwnici (< Proto-Slavic *brъvьnici).